Magnetic excitation of high-Q resonance with split-ring resonators. (25th November 2021) - Yan, Jing-Chun; Zhang, Shi-Qian; Zhang, Yong; Wang, Yu-Lin; Huang, Cheng-Ping
Abstract: Planar split-ring resonators (SRRs) with broken symmetry, excited by the electric field of incident wave, have been widely used to realize the high-Q resonance. In this paper, we report by theory and experiment an alternative scheme to induce the SRR-based high-Q resonance. The proposed scheme utilizes a two-dimensional array of vertical SRRs with vertical air gaps, which enables the excitation of narrow resonance with magnetic field and strong enhancement of local electromagnetic fields. The working mechanism correlates with the strong directional dependence of the dipole radiation (i.e., the elimination of electric-dipole radiation of the SRRs in the propagation direction), rather than the destructive interference due to the structural symmetry breaking. The dependence of Q factor on the structural parameters has also been studied theoretically, suggesting that a Q factor more than 2000 can be achieved. The results may be useful for designing narrow-band filters and sensors in the microwave or THz regime.